Gold-bearing listwaenites in ophiolitic ultramafics from the Eastern Desert of Egypt: Subduction zone-related alteration of Neoproterozoic mantle?. (September 2022) - Hamdy, Mohamed M.; Lasheen, El Saeed R.; Abdelwahab, Wael
Abstract: Dike-like variable listwaenites with significant Au (up to 25 ppm) are exposed along fault zones in serpentinites at Um Khasila-Um Huweitat (Kh-H) and Malo Grim (MG) in central and southern Eastern Desert of Egypt, respectively. The protoliths of serpentinites were mainly Neoproterozoic fore-arc mantle olivine-rich peridotites. The Kh-H serpentinites are similar to those formed in the mantle wedge, but the MG serpentinites are similar to those formed in the subducted oceanic slab. Serpentinization fluids sourced from dehydrated subducted sediments and oceanic crust. However, the Kh-H serpentinites received more lighter fluids mobile trace elements relative to MG serpentinites (av. Ba/Th = 312 vs. 0.79; av. U/Th = 466 vs. 0.018; av. As/Sm = 0.057 vs. 0.76; av. Cs × depleted mantle = 5075 vs. 7272). The Kh-H listwaenites are allometamorphic, formed by the intrusion of gabbro-diorite and the release of the subducted slab-derived CO2 into the mantle wedge serpentinites giving talc-carbonate (Type I) with high K2 O (av. 3.27 wt%), Sr (av. 1131 ppm), Rb (av.165 ppm), Ba (av.407 ppm), and Zr (av. 23 ppm). The MG listwaenites, which have substantially lower K2 O, Na2 O, TiO2, and Al2 O3 concentrations, are autometamorphic and were generated by the loss of SiO2 and addition of CO2 into the subducted serpentinites. With temperature decrease, in Kh-H listwaenites magnesite was overgrown by ankerite, while in MG listwaenites carbonate changed from magnesite to dolomite to calcite. SiO2 -bearing fluids could have mixed from continental crust during Kh-H ophiolite emplacement, forming silica-rich listwaenite (Type III) with enriched K2 O, TiO2, As, Ba, W and Th. This could be linked to carbonation of serpentinites in MG, forming silica-carbonate listwaenite (Type II) with enriched MnO, Sc, Cr, As, Sr, Cs, Ba, Pb, and U. Mixing of silicification fluids with the Kh-H altered serpentinites most likely increased gold concentration in the enclosed listwaenites. In the MG listwaenites, however, there is no correlation between Au content and SiO2 /(CaO + MgO) ratios, indicating that gold was frequently concentrated by the carbonation process. Highlights: Ophiolitic ultramafics are altered along shear zones to listwaenites. Protoliths were harzburgites from mantle wedge (Kh-H) and subducted oceanic slab (MG). Talcification, carbonation and silicification of harzburgites represent the main alteration (listwaenites). Carbonation-silicification in Neoproterozoic mantle of Egypt played a significant role in gold concentrations.